6 - Mother’s Milk, An Ambiguous Blessing in the Bra of AIDS: The Case of’the Chagga in Kilimanjaro - Karen Marie Moland (African Sociological Review, 2004)
HIVIAIDS has renewed the need for a critical interpretation of hreastfeeding in social and cultural terms. The issue that this study addresses is how medically informed knowledge o_f HIV transmission through breastfeeding is interpreted and transformed in a local rural community in Kilimaryaro Region in northern Tanzania. The paper explores the articulation between a medical discourse on risk and a local dis course on motherhood which infrJrms the choice of infant jèeding method. Jt dis eusses the complexities involved in making an appropriate decision on breasiféeding, and argues that breas(feeding must be understood as close/y tied to the cultural elaboration of the female body and of motherhood. lt shows that the body of the mother and the body ()/'the newborn child are subject to close scrutiny and local diagnostic processes. Not breasifèeding is not only perceived as a significant fàilure of motherhood, but also rais es suspicion of a likely HIV positive status on the part of the mother.